O1-S10.05 Cohort study to determine sexually transmitted rectal infections among high-risk men who have sex with men in India. (10th July 2011) - Ranjan, M; Das, A; Narayanan, P; Gurung, A; Risbud, A; Gangakhedkar, R
Abstract : Background: There are few studies on sexually transmitted infections (STIs) among men who have sex with men (MSM) in India to inform the development of appropriate strategies for STI control. This cohort study aimed to determine the prevalence and incidence of rectal gonorrhoea and chlamydia among high-risk MSM in response to standardised interventions in Avahan, the India AIDS Initiative of the Bill & Melinda Gates Foundation. High-risk MSM are self-identified MSM who have large numbers of sex partners and sell sex or practice receptive anal sex. Methods: A cohort of 512 high-risk MSM attending STI clinics in two high HIV prevalence cities of India was recruited in 2008 and followed for four visits over a year. During each visit, rectal swabs were collected during proctoscopic examination and tested for Neisseria gonorrhoeae (GC) and Chlamydia trachomatis (CT) by Roche Amplicor PCR. Participants were provided risk reduction counselling and those with ano-rectal discharge syndrome received treatment as per the national guidelines. In addition, all participants received presumptive treatment for gonorrhoea and chlamydia at the baseline visit. Results: At baseline, rectal GC and/or CT prevalence was 14% and remained consistent over the visits. Of those with laboratory confirmed infections, only 8.2% were clinically diagnosed with ano-rectal discharge syndrome, while the majority (91.8%) did not have relevant symptoms or signs. Participants were followed for a total of 139.3 person years (median—0.25 years, max—1.07 years) during which 1562 visits were made. During the study period, 127 incident infections of rectal GC and CT were found giving an incidence rate of 91.2 per 100 person years. The incidence rate was highest when consecutive visits were within 30 days (241.8 per 100 person years, HR 0.83, p=0.00). There were no significant associations of incidence of rectal gonorrhoea and chlamydia with demographic and behavioural characteristics (Abstract O1-S10.05 table 1 ). Conclusions: A high prevalence of asymptomatic rectal gonorrhoea and chlamydia was observed along with a high incidence rate of these infections among high-risk MSM in India. The persistence of high prevalence of asymptomatic infections remaining even after presumptive treatment at the first visit calls for a review of the periodicity of presumptive treatment in similar clusters of MSM. Consistent condom use and partner treatment need to be re-emphasised.